2011
DOI: 10.1186/2041-7136-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sedentary pastoralism in south India: case study of the Kangayam grassland

Abstract: Kangayam grassland in the tropical region of south India has been sustainably managed for over one hundred and fifty years. In a region with meagre rainfall, growing grass is the farmers' main vocation. Between 1855 and 1881, the majority of government 'wastelands' were given on lease to farmers who organized the land into grazing paddocks and fenced with hedges of Balasmodendron berryi. Numerous wells were dug in the grazing lands to provide water for drinking to animals and to some extent for irrigation. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Involving nitrogen fixing tree species, the system offers immense possibilities of supplementing the nitrogen requirements of crops grown in association, besides providing rich organic matter and improving the soil structure preventing land degradation. Most of the nitrogen fixing trees commonly planted include species of Acacia, Albizia, Hardwickia, Gliricidia, Leucaena, Pongamia, and Sesbania (Solanki and Ramnewaj 1999 Kumar et al 2011) At 5 years of tree age, sorghum (Sorghum bicolor) and groundnut (Arachis hypogaea) yields were higher in lower tree density by 32-57 % in comparison to higher tree density. Tree population did not affect the dry matter production in both the groundnut and sorghum crops at 5 years of tree age.…”
Section: Forest Trees and Arable Crops-based Systemsmentioning
confidence: 97%
See 2 more Smart Citations
“…Involving nitrogen fixing tree species, the system offers immense possibilities of supplementing the nitrogen requirements of crops grown in association, besides providing rich organic matter and improving the soil structure preventing land degradation. Most of the nitrogen fixing trees commonly planted include species of Acacia, Albizia, Hardwickia, Gliricidia, Leucaena, Pongamia, and Sesbania (Solanki and Ramnewaj 1999 Kumar et al 2011) At 5 years of tree age, sorghum (Sorghum bicolor) and groundnut (Arachis hypogaea) yields were higher in lower tree density by 32-57 % in comparison to higher tree density. Tree population did not affect the dry matter production in both the groundnut and sorghum crops at 5 years of tree age.…”
Section: Forest Trees and Arable Crops-based Systemsmentioning
confidence: 97%
“…5.4). Eight species of perennial grasses, 6 annual grasses, 9 legumes, and 16 forbs have been reported in this grazing land (Kumar et al 2011). Acacia leucophloea is the predominant tree species with occasional presence of Acacia nilotica, Acacia planiformis, Albizia amara, Azadirachta indica, and palmyra (Borassus flabellifer) trees.…”
Section: Woodlots As Block Plantationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the remaining 35,709 wells were dug by the farmers in the wastelands held on patta in the last one hundred year. Digging of new wells was also encouraged by the generous loans provided by the British rulers in the form of taccavi advances (Voelcker 1893). The new wells dug were primarily meant to water the animals that remained day in and out for months together between July and February in the grazing paddocks.…”
Section: Role Of Wells In the Grasslandmentioning
confidence: 99%
“…The new wells dug were primarily meant to water the animals that remained day in and out for months together between July and February in the grazing paddocks. Voelcker (1893) observed that anything which induces the people to invest money on the land gives them a permanent interest in the continuance of the English rule. DFID (2002) and Gill (1995) have also observed that security of tenure and ownership play an important role in the sustainability of land.…”
Section: Role Of Wells In the Grasslandmentioning
confidence: 99%